O conceito de amor em Bento XVI e a presença do ágape no direito brasileiro - Milani, Daniela Jorge (2019)
The present work is a dialogue between theology and law on a topic that, being expensive to the first, deserves to find a place of importance in the second. Thus, at first it is sought to clarify the real sense of secularity, avoiding the mistake of closing reason to the wisdom of faith. Being love a word that expresses the most diverse realities, we tried to delimit the concept chosen through the encyclicals of Pope Benedict XVI on the subject, defining type of love here treated as the agape love. It was found, therefore, that this novelty emerged from the evangelical texts as an attitude of gratuitousness towards the other, that he came to be considered a brother, whatever his condition. Love agape is also expressed by words such as brotherly love, mercy, forgiveness and humanizes the understanding of justice, avoiding that it becomes the logic of mutual interest to become the logic of superabundance, responsibility for the other, avoiding that justice becomes an instrument of revenge. In the last chapter it is shown that the vision of justice humanized by agape love is the ideal state of things established by the Brazilian legal system that contemplates principles of equality, fraternity and human dignity in the Federal Constitution. As well, some rules of agape existis in the Brazilian legal order, so that judges of several courts of the country interpret the law in the concrete case from the reality of the agape, that emerges, therefore, important guiding of the jusphilosophical thinking